Migrant women and sexual and gender-based violence at the Colombia-Venezuela border: A qualitative study - Mariana Calderón-Jaramillo; Diana Parra-Romero; Luz Janeth Forero-Martínez; Marta Royo; Juan Carlos Rivillas-García (Elsevier, 2020)
Background: Sexual and Gender-Based Violence (SGBV) affects women and girls in multiple ways. During migration and within humanitarian settings, migrant women and girls are exposed to different forms of SGBV and to higher vulnerabilities compared with those men encounter. Survivors of this kind of violence face challenges in accessing healthcare for reasons that not only include legal status, language barriers, discrimination, misinformation on the availability of healthcare services, but also the growing spread of conservative views regarding sexual and reproductive health which pose a considerable threat to human rights. This study was guided by the question of how humanitarian emergency preparedness and response initiatives within four cities at the Colombo-Venezuelan border are addressing SGBV. The goal of this research was threefold: first, to explain the level of implementation of the second goal of the MISP, which is to prevent and respond to the consequences of sexual violence; second, to assess the availability of services for migrants who have experienced some type of sexual violence; and third, to understand the perceptions of migrants regarding sexual and gender-based violence. Methods and Findings: This study assessed the degree of implementation of the Minimal Initial Service Package (MISP) using a set of tools developed by the Inter-Agency Working Group on Reproductive Health in Crises. This study combined the use of different qualitative methods: i) a literature review; ii) 23 interviews with key informants on sexual and reproductive health; iii) an assessment of 21 health institutions which provide services to migrants; and iv) 24 focus groups with migrants between the ages of 14 to 49 years old (241 participants, of which 121 were women and 120 were men). This research was conducted in four cities at the Colombo-Venezuelan border where there was the highest concentration of migrants. Ethical approval was granted by Profamilia´s Advisory Committee on Research Ethics. Although preventing and managing the consequences of sexual violence is the second objective of the MISP, this study found several barriers for the guarantee of comprehensive healthcare for survivors: Venezuelan migrants do not usually consider that healthcare is a need for them after they have survived sexual violence; SGBV during migration is a common occurrence according to key informants; in three out of four cities there were existing organizations working on SGBV, but not all of them could offer comprehensive healthcare services in response to sexual violence. Conclusions: In this study, we observed that migrants tend to be more exposed to Sexual and Gender-Based Violence due to the normalization of such forms of violence in the Colombian and Venezuelan cultures. Findings suggest that Venezuelan migrants are facing complex SGBV issues during the humanitarian emergency at the Colombia-Venezuela border. Recommendations include local health systems response teams, governments and host communities working together to address early access to prevention, healthcare, and protection services for the survivors of SGBV; eliminating barriers in access to essential and comprehensive equity-oriented healthcare services; developing the skills and capacities of healthcare services professionals around the proper management of SGBV; and countering misinformation, lowering the stigma associated with migrants in host communities, and broadening migrant´s perceptions of SGBV, gender roles, and xenophobia.